The Use of Bluetooth in the Intelligent Sensor Network (International Journal of Innovative Research in Computer Science & Technology, 2022)
Because they would be running on lesser  power but also most likely without the support of a central  system, potential ubiquitous computing gadgets would  need to interface with other smart devices on an ad hoc  basis. However, no one communication technique has yet  to emerge as a viable contender in the area of ubiquitous  computing: numerous present wireless communication  methods seem to be deficient in robustness, use excessive  levels of energy, or need the utilization of networks to be  competitive. We installed a Smart device into the first  iteration of a multi sensor device connected as part of a  National Smart-Its research project, which was built to  assess the suitability of the newest but also most potential  Bluetooth module for particular connection requirements.  Despite the reality that Bluetooth allows for reliable and  easy ad hoc communication, preliminary research suggests  that the Bluetooth system might benefit from better support  for asymmetrical communication and, in especially, slave to-slave transmission.
Keywords: Bluetooth; Sensor Network; Smart-Its; Universal Asynchronous Receiver-Transmitter (UART); Wireless-HART (Highway Addressable Remote Transducer)